EDUCATIONAL STATUS OF INDIAN WOMEN: A HISTORICAL STUDY - Anjum, Shabana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Girls’ education is a great opportunity for the social and economic development of India. Educated girls are the weapons that have a positive impact on the Indian society through their contribution in their home and professional fields. They are the reason for a better economy in the country and society. The objectives of this paper are: to evaluate the current status and challenges of girls’ education in India; and to provide possible suggestions to overcome the challenges of girls’ education in India. To conduct this study the researcher has used a variety of articles, reports, research papers, books, government websites and online materials. This paper is divided into four parts. The first part highlights the historical context and importance of girls’ education in India. The second part discusses the current status of girls’ education in India. The third part describes in detail the major steps taken by the Indian government to improve girls’ education and the various challenges of girls’ education. The last section gives suggestions to remove the barriers to girls’ education in India. The paper concludes by saying that girls’ education is in a much worse state at primary and secondary level than higher education. Girls’ enrollment rate has declined from 2012 to 2015 at primary and secondary level, but girls’ gross enrollment ratio has increased from 2012 to 2015 at higher education level. Parental attitude, lack of infrastructure, lack of security, superstitions related to girls, socio-economic status of parents are the major challenges to promote girls’ education in India. It is suggested in this paper that higher authorities, community members, NGOs and all citizens of India should take responsibility to eliminate various barriers related to girls’ education from our society.